PENGARUH SUKU BUNGA KREDIT, INFLASI, DAN NILAI TUKAR TERHADAP JENIS PENYALURAN KREDIT - Eltania, Merry (Contemporary Studies in Economic, Finance and Banking, 2022)
One of the ways to handle the impact of the Covid-19 pandemic on the economic sector is by increasing credit distribution, which is considered capable of encouraging an increase in a country's economic activity. This quantitative study aims to identify the effect of credit interest rate, inflation, and exchange rate on the types of commercial banks’ credit distribution in Indonesia using multiple linear regression. This research uses secondary. Information about interest rate was obtained from Statistics Indonesia, while data about inflation, exchange rate, and the three types of credit distribution channel was acquired form Bank Indonesia. The types of credit are consumptive, investment, and working capital credit. This study finds that interest rate has a significant and negative effect on the three types of credit distribution channel and that inflation positively and significantly affects the three types of credit distribution channel. However, the effect of inflation on the credit channel is different from the theory and the researcher’s presumption, similar to the effect of exchange rate. Exchange rate positively and significantly affects investment credit, but it does not significantly influence consumptive and working capital credit.